Nanofluid application in electric motor cooling / Sree Rama Dasson Velayudlan - Sree Rama Dasson, Velayudlan (2012)
Electronics devices such as electric motors generate enormous amount of heat, which disturbs the normal performance of the devices and reduces their reliability. This temperature rise has to be limited for two reasons: mechanical stress and the deterioration of the insulating materials. Heat generation is also caused the life span of the motors to decrease and its cause a new replacement which normally cost high. To overcome the heat transfer problems, many cooling methods were applied to the electric motors but still it cannot be solve effectively due to some limitations in these methods. To improve the heat transfer rate, the water or the other liquids such as ethylene glycol were dispersed and suspended with nanoparticles. This new class of heat transfer fluids is called nanofluids where the high thermal conductivity solid particles were mixed into the heat transfer liquids to gain a higher heat transfer rates. Therefore, a study was conducted and encompasses in cooling of the electric motors by nanofluids. The study has shown that by replacing nanofluids to the base fluids, the heat transfer rate can be improved. Also, this study has opened the opportunity for the researchers to do researches under nanofluids for cooling purposes.